BRIDGING PROFESSIONAL IDENTITY AND DIGITAL PLATFORMS: A COMPREHENSIVE STUDY OF SELF-MARKETING AND CAREER DEVELOPMENT - Aram Qadir; Jacek Binda (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
— Self-marketing has gained particular relevance in the digital age, where personal branding has become a crucial component of professional self-realization. This study adopts a comprehensive approach that combines theoretical analysis of self-marketing with empirical data collected through an online survey conducted among students from higher education institutions in KRG. The article delineates the key elements of self-marketing essential for developing a personal brand and the tools for their implementation. Depending on specific objectives and chosen methodologies, the strategies of self-marketing are categorized into distinct types, ensuring flexibility and adaptability in their application. Particular emphasis is placed on digital platforms as vital channels for promoting personal brands, where the integration of professional and personal identities within the media space is increasingly evident. The research findings synthesize and systematize the primary digital platforms utilized for personal brand development while identifying barriers to implementing self-marketing strategies and addressing ethical considerations in personal brand promotion. It is demonstrated that active self-marketing facilitates professional self-realization but necessitates a mindful approach to preserve authenticity. A marketing study was conducted to empirically assess the effectiveness of self-marketing, analyzing its impact on student's career prospects and readiness for professional self-realization. This research identified the key factors contributing to personal brand development and formulated practical recommendations for leveraging self-marketing in professional growth. The article introduces new evidence underscoring the significance of digital platforms for building personal brands among young students. The study's hypothesis posits that the effectiveness of self-marketing strategies depends on awareness of their influence on career prospects and the selection of appropriate tools. This work's theoretical contribution lies in advancing knowledge of self-marketing as a personal marketing strategy, while its practical value is reflected in the findings' applicability for improving career positioning. This empirical investigation provides a foundation for further analysis with an expanded sample and the exploration of the algorithmic effects of digital platforms on content visibility.